Selective excitation of vibrational modes and probe for asymmetric intramolecular energy redistribution. (2nd April 2019) - Liu, Xiaosong; Zhang, Wei; Song, Yunfei; Zheng, Zhaoyang; Lv, Zhe; Yang, Yanqiang
Abstract: Femtosecond time- and frequency-resolved coherent anti-Stokes Raman scattering spectroscopy was performed on liquid nitrobenzene (NB) to explore intramolecular vibrational energy redistribution in the electronic ground state. While high-frequency C–H stretching vibrational modes ( v CH ∼ 3080 cm −1 ) were selectively excited, vibrational energy redistribution to the nitro group and phenyl ring breathing modes ( v NO 2 s ∼ 1335 cm −1, v NO 2 a s ∼ 1514 cm −1 and v C C ∼1584 cm −1 ) was described. While lower frequency modes of the nitro group and phenyl ring breathing were selectively excited, vibrational energy redistribution to C–H stretching modes with higher efficiency was detected. There is counter-intuitive vibrational energy flow in NB. Vibrational energy redistribution was discussed in the view of coherent population transfer between parent modes. Coherent coupling of these relevant modes and the selectivity of vibrational energy redistribution were further analyzed from the viewpoint of vibrational symmetry.